Leishmania parasite detection and quantification using PCR-ELISA - Kobets, Tetyana; Badalová, Jana; Grekov, Igor; Havelková, Helena; Svobodová, Milena; Lipoldová, Marie (Nature protocols, 2010)
This protocol describes an improved and optimized PCR-ELISA method for detection and quantification of Leishmania parasites in host tissues. Unlike other DNA-based assays, this method uses digoxigenin- and biotin-labeled primers. This eliminates the need for a separate step of hybridization of the PCR product with labeled probes. The PCR product is detected using sandwich ELISA with antidigoxigenin-detecting antibodies. Primers are complementary to the kinetoplast minicircle conserved region of parasite DNA, allowing the detection of several Leishmania species. For measurement of a wide range of parasite concentrations, +/-25 cycles were optimal. The sensitivity of this technique is 0.3 fg of parasite DNA per reaction in 40-cycle PCR-ELISA, corresponding to 0.004 parasites. DNA preparation by a standard TRI reagent procedure takes about 4 h. When DNA is prepared, a single person can test a large number of samples (at least 150) in a maximum of 7 h. This method might also be suitable for detecting and quantifying other pathogens, especially for detecting small differences in pathogen numbers.
Keywords: Mice; sekvence nukleotidů; Base Sequence; Enzyme-Linked Immunosorbent Assay; DNA, Protozoan; DNA Primers; Leishmaniasis; Polymerase Chain Reaction; Leishmania major; ELISA; myši; DNA primery; polymerázová řetězová reakce; Animals; protozoální DNA; Leishmania; zvířata; leishmanióza